Age-Related Central Auditory Processing Disorder, MCI, and Dementia in an Older Population of Southern Italy. (August 2020) - Sardone, Rodolfo; Battista, Petronilla; Donghia, Rossella; Lozupone, Madia; Tortelli, Rosanna; Guerra, Vito; Grasso, Alessandra; Griseta, Chiara; Castellana, Fabio; Zupo, Roberta; Lampignano, Luisa; Sborgia, Giancarlo; et al.
Objective: We explored the associations of age-related central auditory processing disorder (CAPD) with mild cognitive impairment (MCI) and dementia in an older population-based cohort in Apulia, Southern Italy (GreatAGE Study). Study Design: Cross-sectional data from a population-based study. Setting: Castellana Grotte, Bari, Italy. Subjects and Methods: Between 2013 and 2018, MCI, dementia, age-related CAPD (no disabling hearing loss and <50% score on the SSI-ICM test [Synthetic Sentence Identification–Ipsilateral Competing Message]), neurologic and neuropsychological examinations, and serum metabolic biomarkers assays were investigated on 1647 healthy volunteers aged >65 years. Results: The prevalences of age-related CAPD, MCI, and dementia were 14.15%, 15.79%, and 3.58%, respectively. Among the subjects with MCI and dementia, 19.61% and 42.37% had age-related CAPD. In the regressive models, age-related CAPD was associated with MCI (odds ratio, 1.50; 95% CI, 1.01-2.21) and dementia (odds ratio, 2.23; 95% CI, 1.12-4.42). Global cognition scores were positively associated with increasing SSI-ICM scores in linear models. All models were adjusted for demographics and metabolic serum biomarkers. Conclusion: The tight association of age-related CAPD with MCI and dementia suggests the involvement of central auditory pathways in neurodegeneration, but it is not clear which is the real direction of this association. However, CAPD is a possible diagnostic marker of cognitive dysfunction in older patients.